Exposure science and occupational health: insights from ISES 2022 [editorial] - Almeida-Silva, Marina (2024)
The annual meeting of the International Society of Exposure Science – From Exposure to Human Health: New Developments and Challenges in a Changing Environment – took place from 25 to 29 September 2022 in Lisbon, Portugal. The conference aimed to promote information sharing and facilitate discussion on exposure sciences and related fields in the context of the changing environment, especially how we – as exposure scientists - can better understand and respond to the complex and multidisciplinary issues in exposure and environmental health through sciences and policies. This research topic now presents insights on exposure science and occupational health that were presented during the ISES 2022 conference covering all aspects of occupational exposure science. The ISES 2022 conference resulted in many abstracts being submitted (more than 450 submissions) describing the findings of new research on exposure science. The final participation numbers were 421 in-person attendees and 35 virtual attendees. It should be mentioned that 93 (20%) attendees were students or new researchers. The main geographical origins of our attendees were North America (42%) followed by Europe (39%). Modern exposure science is rooted in the industrial hygiene and radiation health physics practices of the last century and exposure science continues to play an important role in occupational health. Today, an individual may encounter a wide range of agents that directly or indirectly result in some form of adverse effect or harm. Generally referred to as “stressors,” these agents can be chemical, physical, biological, or psychosocial, as well as mixtures thereof. Exposure science is the distinct discipline that encompasses the study of receptors and their behaviors related to contact with such stressors, the nature and extent of such contact, and the fate of these stressors over space and time.